WOUND INFECTION - SISTEMATIC LITERATURE REVIEW - Edmar Jorge Feijó; Isabel Cristina da Fonseca Cruz; Dalmo Valério Machado de Lima (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Objectives: To review, identify and analyze the main aspects of the scientific production of healthcare professionals about wound infection, providing an update of relevant technical information for improving their capabilities for a better injury care. Methods: This is a review of the literature contained at bireme and pubmed databases published from 2002 to 2008. Results: The results revealed nineteen publications and all the information data were subjected into thematic analysis, divided into three distinct categories: the best evidence for the prevention and control of the infections, the association between infections and the places where the injuries are present and the indication of the best healing implementation techniques. Conclusion: There is a consensus that professional nurses must always update themselves for the promotion of the correct epidemiological studies about the patient's social and demographic profiles in order to improve adequate identification of the microorganisms probably concerned to these infections. The development of new standardized protocols leading to uniform practices into reliable results are necessary for delineating a pattern of a specialized nursing care in the search for the total quality being the nurse the prime agent in this question.